Development and Evaluation of eHealth Services Regarding Accessibility: Scoping Literature Review - Marika Jonsson; Stefan Johansson; Dena Hussain; Jan Gulliksen; Catharina Gustavsson (JMIR Publications, 2023)
BackgroundAccessibility is acknowledged as a key to inclusion in the Convention of Rights for People with Disabilities. An inaccessible design can result in exclusion from eHealth and cause disability among people who have impairments. ObjectiveThis scoping literature review aimed to investigate how eHealth services have been developed and evaluated regarding accessibility for people with impairments. MethodsIn line with Arksey and O'Malley's framework for scoping studies and using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), we conducted a search in 4 databases (PubMed, Scopus, IEEE, and Web of Science) in October 2020 and an update of the search in June 2022. The search strategy was structured according to the PICO model as follows: Population/Problem, digital accessibility for users with impairment; Intervention, health care delivered by any digital solution; Comparison, not applicable; Outcome, use of and adherence to (1) Web Content Accessibility Guidelines (WCAG), (2) other accessibility guidelines, and (3) other means, for designing or evaluating accessibility in eHealth services. A Boolean search was conducted by combining terms related to accessibility and eHealth. All authors participated in screening abstracts according to the eligibility criteria. Each publication, containing a potentially relevant abstract, was read (full text) and assessed for eligibility by 2 authors independently and pairwise. Publications deemed eligible were read by all authors and discussed for consensus. ResultsA total of 8643 publications were identified. After abstract screening, 131 publications remained for full-text reading. Of those, 116 publications were excluded as they did not meet the eligibility criteria. Fifteen publications involving studies of 12 eHealth services were included in the study. Of the 15 publications, 2 provided a definition of accessibility, 5 provided an explanation of accessibility, and 8 did not provide any explanation. Five publications used the WCAG to evaluate accessibility when developing eHealth services. One publication used International Organization for Standardization (ISO) 29138, ISO 2941, and ISO/International Electrotechnical Commission (IEC) 30071-1 standards together with the Spanish Association for Standardization (UNE) 139803 standard. Eleven publications used other means to address accessibility, including text-level grading; literature review about accessibility; user tests, focus groups, interviews, and design workshops with target groups of patients, relatives, and health care professionals; and comparative analysis of existing technical solutions to provide information about useful requirements. ConclusionsAlthough a clear definition of accessibility can enhance operationalization and thus measurability when evaluating accessibility in eHealth services, accessibility was insufficiently defined in most of the included studies. Further, accessibility guidelines and standards were used to a very limited extent in the development and evaluation of eHealth services. Guidelines for developing complex interventions that include guidance for accessibility are motivated to ensure that accessibility will be considered systematically in eHealth services.